Temporary Migration Projects, Special Rights and Social Dumping - Ottonelli, Valeria (Ethical theory and moral practice, 2019)
It is often argued that in order to prevent migration from having social dumping effects, a strict enforcement of equal labour and welfare rights for both migrants and local workers is required. However, we claim that the specific circumstances of those migrants who engage in temporary migration may require a regime of special rights and labour standards that protect and further their distinctive interests and needs. We defend this claim by appealing to the principle that labour and welfare rights should accommodate the life plans of workers and we show that not only these special arrangements are fairer to the migrants involved, but they could also help to prevent social dumping.